Using periodic hydrologic and geochemical sampling with limited continuous monitoring to characterize remote karst aquifers in the Kaweah River Basin, California, USA. Issue 19 (6th June 2016) - Tobin, Benjamin W.; Schwartz, Benjamin F.
Abstract: Hydrogeologic field work in remote settings is often challenging: assessing spring behaviour and aquifer characteristics can be expensive in both time commitment and resources needed to assess these systems. In this study, we document the hydrology and geochemistry of 47 perennial karst springs in the Kaweah River, a mountain river basin in the Sierra Nevada, California. After preliminary hydrogeochemical characterization and grouping, selected springs were continuously monitored to further assess aquifer characteristics in each group. Later, in areas without previous dye‐tracing work, traces were conducted to establish connections between large sinking streams and springs. The springs have a wide range of inter‐spring and intra‐spring variability in discharge and geochemistry. We assessed this variability by performing statistical comparisons with spring chemistry and principal components analysis of all measured variables. Results show that springs can be divided into two distinct groups: high elevation springs of the Mineral King Valley and lower elevation springs throughout the rest of the basin. Continuous discharge, temperature and specific conductivity data from four springs (two from each group) were then used to characterize the hydrograph recession behaviour of springs in each group. Both groups showed statistically similar baseflow recession slopes, suggesting that both groups contain baseflow storage compartments with similar hydrogeologic properties. The biggest difference between each group is the variability in amount of water remaining in the aquifer during baseflow conditions. High elevation springs have lower baseflow discharges, relative to peak flow, than lower elevation springs, despite the fact that more precipitation falls at higher elevation. This is likely caused by differences in the amount of soil and epikarst storage, which are related to recent geomorphic events: high elevation aquifers were glaciated as recent as 41 thousand years ago (kya), while there is no evidence that low elevation aquifers were glaciated. As a result, lower elevations have developed thicker soils, weathered bedrock and epikarst. Copyright © 2016 John Wiley & Sons, Ltd.